Heat Transfer Problems in Orthopaedics - Stańczyk, M.; Telega, J.J. (Engineering Transactions, 2003)
The present paper presents a comprehensive review of the heat transfer problems in or-thopaedics. The emphasis is put on presenting clinically relevant issues along with the purpose and motivation for studying the presented problems. The available experimental methods and results are presented and the modelling approaches are described – mathematical formulations and numerical results. The first of the problems studied is the bone cement heating during cemented implantations, special attention being paid to modelling the kinetics of the acrylic bone cement polymerisation. Next, the heat production during drilling and sawing of the bone is discussed. Eventually, the results concerning frictional heating of the articulating joints are presented.